(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Bad breath is a problem that affects every second person in the world. Bad breath often causes loss of self-confidence and prevents communication. Bad breath can be constant or appear from time to time, for example, on an empty stomach. This phenomenon is usually the first sign of dental problems and diseases of internal organs. In medicine, bad breath is called "halitosis".